Kemampuan Representasi Matematis Siswa melalui Model Problem Based Learning pada Materi Lingkaran dengan Konteks Kepramukaan di SMP - Aslamiah, Suaibatul; Johar, Rahmah; Maidiyah, Erni (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
Mathematical representation ability is a useful ability for students to develop and optimize their mathematical abilities. The real situation shows that the importance of the ability of mathematical representation has not been matched by student achievement. This condition can be solved by applying problem based learning model to learning in a context that is familiar to students such as scouts. The aim of this research is to explain the ability of students? mathematical representation through the Problem Based Learning model with scouts context on circle material at SMPN 8 Banda Aceh. This research used qualitative approach with a type of research is descriptive. Data obtained through tests of student? mathematical representation abilities and interviews. The ability of students? mathematical representations was analyzed by utilizing the data obtained in student learning in groups through PBL model and data of result test after the application of PBL model. The achievement of this research is the ability of students? mathematical representation during learning with PBL model in groups is accordance with the ability of students? mathematical representation after applying the PBL model. The mathematical representation ability of high ability students is able to complete all of the indicators of the mathematical representation ability, students who are in the medium ability only complete indicators of visual and symbolic representation, and low ability students only able to complete indicator of visual representation, although not perfectly.